1995
DOI: 10.1016/0168-6496(95)00022-3
|View full text |Cite
|
Sign up to set email alerts
|

The ammonia-oxidizing nitrifying population of the River Elbe estuary

Abstract: The ammonia‐oxidizing bacterial population of the tidal River Elbe was analysed. In the freshwater section of the river, abundance was generally at a magnitude of 104 cells per g dry weight and 103 cells per ml in sediments and in water samples, respectively. In the brackish water region, counts decreased drastically with the increase in salinity caused by the low level of abundance of ammonia‐oxidizers in the seawater. The contribution of attached ammonia‐oxidizers to the total number ranged between 50 and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
104
3
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 1 publication
14
104
3
1
Order By: Relevance
“…The ratio of AOA to AOB was larger than 1 at about 75% of the sites, and the greatest value of this ratio was primarily observed in the Hengshui and Xingtai reaches. In the natural environment, AOA are generally more abundant than AOB (Wessén et al, 2011;Leininger et al, 2006;Wu et al, 2010), and the abundance of AOA (Mincer et al, 2007) and AOB (Stehr et al, 1995) in the water column is commonly in the range of 10 2 to 10 5 gene copies/mL, which is consistent with the results of the present study.…”
Section: Physicochemical Characteristicssupporting
confidence: 92%
“…The ratio of AOA to AOB was larger than 1 at about 75% of the sites, and the greatest value of this ratio was primarily observed in the Hengshui and Xingtai reaches. In the natural environment, AOA are generally more abundant than AOB (Wessén et al, 2011;Leininger et al, 2006;Wu et al, 2010), and the abundance of AOA (Mincer et al, 2007) and AOB (Stehr et al, 1995) in the water column is commonly in the range of 10 2 to 10 5 gene copies/mL, which is consistent with the results of the present study.…”
Section: Physicochemical Characteristicssupporting
confidence: 92%
“…Earlier studies have suggested that nitrite (Sahan and Muyzer, 2008) and pH (Nicol et al, 2008) may be determining factors in the niche differentiation between AOA and AOB, whereas salinity and hydrological factors have been suggested to have an influence on the structure and dominance of AOA or AOB communities (Stehr et al, 1995;Cebron et al, 2003;Francis et al, 2003;Bernhard et al, 2005;Dang et al, 2008;Mosier and Francis, 2008). This suggests that there are likely to be a number of potentially confounding environmental factors shaping ammonia oxidising communities in estuarine sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from a variety of habitats document that AOB communities vary over space (Kowalchuk and Stephen, 2001) and that this variation is correlated with a variety of factors, including salinity (Stehr et al, 1995;Sahan and Muyzer, 2008), temperature (Avrahami and Conrad, 2005;Fierer et al, 2009), nutrients (Webster et al, 2002;Mosier and Francis, 2008), plant composition (Briones et al, 2002;Mintie et al, 2003;Dollhopf et al, 2005), soil moisture (Hastings et al, 2000) and pH (Kowalchuk et al, 2000;Nicol et al, 2008). Field experiments confirm that pH (Stephen et al, 1998;Backman et al, 2003) and nitrogen availability (Phillips et al, 2000;Webster et al, 2002) can directly influence AOB composition and/or abundance.…”
Section: Introductionmentioning
confidence: 95%